Faktor-Faktor Yang Mempengaruhi Penggunaan Pengisian Partograf Di BPM Swasta Wilayah Banjarmasin - isnaniah isnaniah; Tri Tunggal; Rita Kirana (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
The phenomenon that occurs, states that the policy on the use of the partograph has not fully run according to the procedure. The practice midwife actually already knows the policy, but has not fully done it well. In its implementation, midwives do not use partograph completely, correctly and on time. The results of the study were 54 respondents, 12 respondents (22%) who lacked partograph utilization, 44 respondents (81.5%) had good knowledge, 46 respondents (85.2%) had a positive attitude and 40 respondents (74.1%) had good skills. proficient, the results of the statistical test have no relationship between midwife's knowledge of partograph and the use of partograph filling and there is a meaningful relationship between attitudes and skills with the use of partographs in Banjarmasin's private BPM The conclusion in this study is that there is no significant relationship between knowledge and the use of partographs, but there is a meaningful relationship between attitudes and skills with the use of partographs in the Banjarmasin BPM private sector and suggested BPM work area responsibilities to supervise recording and reporting Keywords: Knowledge, Attitudes, Skills, Partographs